product rule:
dy/dx = x(2e^2x) + e^2x
=e^2x ( 2x +1)
`
2006-12-01 04:09:56
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
Essentially, you're asking how to find the derivative of x*e^2x, which does involve the product rule, which is:
the derivative of U*V = the derivative of U * V + U * the derivative of V.
Given that the derivative of x = 1, and
that the derivate of e^K = (the derivative of K) * e^K...
U = x
V = e^2x
solution = (the derivative of U) * V + U * (the derivative of V)
= (1) * e^2x + ( x * 2e^2x)
= 2xe^2x + e^2x
= (2x+1)e^2x
2006-12-01 12:14:16
·
answer #2
·
answered by TankAnswer 4
·
1⤊
1⤋
why do you need to find it?
its written in your question!
i always find the best method is to look in that last place you had it! in this case written above all the answers!
2006-12-01 12:11:45
·
answer #3
·
answered by Nigi-magic 3
·
1⤊
1⤋
No clue but maybe the following website will help...
2006-12-01 12:11:51
·
answer #4
·
answered by Sir think alot, @ your service. 2
·
1⤊
1⤋
What are you solving for?
2006-12-01 12:11:06
·
answer #5
·
answered by mitzireeves 2
·
1⤊
1⤋